Epitope specificity of spontaneous and induced thyroglobulin autoantibodies in the rat. - De Assis-Paiva, H J (1988)
We have investigated the epitope specificities of rat thyroglobulin (Tg) autoantibodies arising either spontaneously in BB hybrid and BB rats or following induction in normal rats with thyroglobulin and adjuvant. Using a panel of thyroglobulins from different animal species it was possible to identify three different patterns of reactivity. These were: 1) recognition of all species of thyroglobulin; (2) recognition restricted to rat and mouse thyroglobulins and 3) recognition biased towards dog, rat and mouse thyroglobulins. Furthermore, using human thyroglobulin manifesting different levels of iodination, it was possible to show that sera with recognition pattern 1 recognized the iodination site of thyroglobulin and that this was inhibitable by thyroxine. Taken together these data provide evidence of restricted epitope recognition by Tg autoantibodies in the rat.